Music Engineering as a Novel Strategy for Enhancing Music Enjoyment in the Cochlear Implant Recipient - Gavriel D. Kohlberg; Dean M. Mancuso; Divya A. Chari; Anil K. Lalwani (Behavioural Neurology)
Objective. Enjoyment of music remains an elusive goal following cochlear implantation. We test the hypothesis that reengineering music to reduce its complexity can enhance the listening experience for the cochlear implant (CI) listener. Methods. Normal hearing (NH) adults (N=16) and CI listeners (N=9) evaluated a piece of country music on three enjoyment modalities: pleasantness, musicality, and naturalness. Participants listened to the original version along with 20 modified, less complex, versions created by including subsets of the musical instruments from the original song. NH participants listened to the segments both with and without CI simulation processing. Results. Compared to the original song, modified versions containing only 1–3 instruments were less enjoyable to the NH listeners but more enjoyable to the CI listeners and the NH listeners with CI simulation. Excluding vocals and including rhythmic instruments improved enjoyment for NH listeners with CI simulation but made no difference for CI listeners. Conclusions. Reengineering a piece of music to reduce its complexity has the potential to enhance music enjoyment for the cochlear implantee. Thus, in addition to improvements in software and hardware, engineering music specifically for the CI listener may be an alternative means to enhance their listening experience.